2023
DOI: 10.1002/hipo.23539
|View full text |Cite
|
Sign up to set email alerts
|

Single neurons in the human medial temporal lobe flexibly shift representations across spatial and memory tasks

Abstract: Investigations into how individual neurons encode behavioral variables of interest have revealed specific representations in single neurons, such as place and object cells, as well as a wide range of cells with conjunctive encodings or mixed selectivity. However, as most experiments examine neural activity within individual tasks, it is currently unclear if and how neural representations change across different task contexts. Within this discussion, the medial temporal lobe is particularly salient, as it is kn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Interesting evidence that in humans medial temporal lobe neurons can respond differently in different tasks (navigation vs. n-back memory) was presented in this Special Issue (Donoghue et al, 2023). There is some consistent evidence in macaques, as follows.…”
Section: Task-dependent Activity By Primate Including Human Hippocamp...mentioning
confidence: 84%
See 4 more Smart Citations
“…Interesting evidence that in humans medial temporal lobe neurons can respond differently in different tasks (navigation vs. n-back memory) was presented in this Special Issue (Donoghue et al, 2023). There is some consistent evidence in macaques, as follows.…”
Section: Task-dependent Activity By Primate Including Human Hippocamp...mentioning
confidence: 84%
“…Several contributions to the Special Issue of Hippocampus (2023) provide evidence that many primate hippocampal neurons respond to the location being viewed "out there," not the place where the individual is located (Corrigan et al, 2023;Rolls, 2023b;Wirth, 2023;Zhu et al, 2023). Complementary evidence is also available for humans, in that in another paper in this Special Issue of Hippocampus, it was found that significant numbers of spatial view cells but not a significant number of place cells were found in the medial temporal lobe in a VR navigation task to the remembered location in a scene of a Treasure Chest (Donoghue et al, 2023). The spatial coordinates of these view cell representations are considered next.…”
Section: View Cell Spatial Coordinates: Allocentric Versus Facing Dir...mentioning
confidence: 98%
See 3 more Smart Citations